2015
DOI: 10.1142/s0218810415500057
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathic Pain in Brachial Plexus Injury

Abstract: Our study showed that the prevalence of neuropathic pain was high in brachial plexus injured patients. Therefore, surgeons should be aware of this common, yet underestimated, problem in brachial plexus injured patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
17
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 37 publications
1
17
0
1
Order By: Relevance
“…Allodynia, hypersensitivity and electric-like discharges are present at the border between the normal and affected dermatomes [17,[26][27][28][29], particularly between T 1 and T 2 at the posterior aspect of the elbow [26].The pain severity correlates with the magnitude of the brachial plexus injury [2,3] and to the number of avulsed nerve roots [2-4, 21, 26, 30-33], particularly when the lower roots are affected [24,34,35]. Nevertheless, Bertelli et al [21] found that in isolated C 8 and T 1 nerve root avulsions, there was no pain at all.The pain does not appear immediately after the injury but a few days later [24] and no longer than 3 months after it [5, 6, 24, 26,35,36].The neuropathic pain can be associated with phantom [37] or stump pain [38] in case of upper limb amputation, or to complex regional pain syndrome (CRPS) [6], inducing a complex pain condition rather difficult to control [19,30,31].Self-mutilation has been described in 5-29% of obstetric brachial plexus injury cases [39,40].The quality of life is seriously impaired with sleep disorders, family troubles, unemployment, chronic depression and social withdrawal [2, 5, 6, 17, 21,[41][42][43][44]. Additionally, the chronic pain is a further hindrance to comply with a good rehabilitation programme, impairing a possible functional recovery [6,45,46].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Allodynia, hypersensitivity and electric-like discharges are present at the border between the normal and affected dermatomes [17,[26][27][28][29], particularly between T 1 and T 2 at the posterior aspect of the elbow [26].The pain severity correlates with the magnitude of the brachial plexus injury [2,3] and to the number of avulsed nerve roots [2-4, 21, 26, 30-33], particularly when the lower roots are affected [24,34,35]. Nevertheless, Bertelli et al [21] found that in isolated C 8 and T 1 nerve root avulsions, there was no pain at all.The pain does not appear immediately after the injury but a few days later [24] and no longer than 3 months after it [5, 6, 24, 26,35,36].The neuropathic pain can be associated with phantom [37] or stump pain [38] in case of upper limb amputation, or to complex regional pain syndrome (CRPS) [6], inducing a complex pain condition rather difficult to control [19,30,31].Self-mutilation has been described in 5-29% of obstetric brachial plexus injury cases [39,40].The quality of life is seriously impaired with sleep disorders, family troubles, unemployment, chronic depression and social withdrawal [2, 5, 6, 17, 21,[41][42][43][44]. Additionally, the chronic pain is a further hindrance to comply with a good rehabilitation programme, impairing a possible functional recovery [6,45,46].…”
mentioning
confidence: 99%
“…Additionally, the chronic pain is a further hindrance to comply with a good rehabilitation programme, impairing a possible functional recovery [6,45,46]. Among all the disabilities induced by the brachial plexus injury, the pain has been found to be the symptom that most negatively affects the quality of life [47].Treatment of this chronic pain can be troublesome, as the response to the different treatment modalities is poor and not all of them allow preservation of the remaining upper limb function [2, 5,48].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Brachial plexus avulsion (BPA) induces intermittent shooting pain and a characteristic persistent oppression, which is usually difficult to cure [6]. The pain could be experienced as a feeling of compression or burning [7]. The mechanisms involved in chronic neuropathic pain include the secretion of inflammatory cytokines, the expression of pain-associated proteins, and the activity of astrocytes [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Post‐traumatic neuropathic pain can occur from a variety of traumatic aetiologies, commonly trauma during surgery (such as chronic limb pain following amputation, or failed back surgery syndrome), or an accident producing nerve trauma such as brachial plexus avulsion. Incidence of chronic pain in these groups can be as high as 76% in brachial plexus avulsion , 10–40% following lumbar disc surgery and 60% in the form of phantom pain after limb amputation producing a significant burden of disease. In a proportion of these patients, the pain is refractory to pharmacological therapy.…”
Section: Introductionmentioning
confidence: 99%